The Wulanmoren Accretionary Complex Unravels Early Devonian to Late Triassic Multiple‐Arc Amalgamation in the Tianshan Orogen (NW China). Issue 1 (4th January 2023) - Zhao, Tongyang; Xiao, Wenjiao; Mao, Qigui; Yang, He; Abuduxun, Nijiati; Li, Ping
Abstract: Reconstructing the tectonic architecture of the southern Altaids is of great importance to piece together the continental growth history of the Central Asian continent. In this paper, we address the subduction‐accretion process of the Paleo‐Tianshan Ocean, one branch of the South Tianshan Ocean, in the southern Altaids, through a detailed geological and geochemical investigation of the Wulanmoren Accretionary Complex (WAC). The WAC is composed of ophiolitic mélanges, ocean plate stratigraphy mélanges, and turbiditic coherent units. In this study, we present key geological, petrological, and geochemical evidence indicating back‐arc and ocean island affinity of the igneous rocks of the WAC. Zircon U‐Pb dates of these rocks ages range between 380.2 ± 1.3 and 302.0 ± 5.3 Ma. The sedimentary matrix units of the mélanges were deposited in the Early Devonian (∼405 Ma) to the Late Triassic (∼222 Ma), rather than Silurian strata as previously thought. However, the ages of some detrital zircons in the sedimentary matrix are Precambrian, pointing to a complex evolution involving multiple ocean island terrains and island arcs of different ages that accreted from the mid‐Paleozoic to the Early Mesozoic. Plain Language Summary: Well‐exposed rock outcrops of the Wulanmoren Accretionary Complex (WAC) offer an ideal opportunity to solve the enigma of the evolutionary history of the Paleo‐Tianshan Ocean (PTO) of Central Asia. We report field observations, geochemistry, and geochronology of the WAC in the southern Altaids, pointing to multiple tectonic settings of ages spanning from the Early Devonian (∼405 Ma) to the Late Triassic (∼222 Ma). These reconstructions suggest closure time of the PTO occurred post‐Triassic. Based on detrital zircons provenance analysis, we propose a multi‐island ocean model to explain the tectonic evolution of the PTO in the time period studied. Key Points: The Wulanmoren Accretionary Complex was composed of ophiolitic mélanges, ocean plate stratigraphy mélanges, and coherent units The Late Paleozoic MORB‐like and OIB‐type basalts, and ∼222 Ma coherent units indicate closure of the Paleo‐Tianshan Ocean occurred post‐Triassic The southern Paleo‐Asian Ocean was an archipelago with several subduction systems which is similar to the modern southwest Pacific